2017
DOI: 10.1371/journal.pone.0170397
|View full text |Cite
|
Sign up to set email alerts
|

Is your dog empathic? Developing a Dog Emotional Reactivity Survey

Abstract: Dogs' seemingly empathic behaviour attracts general and scientific attention alike. Behaviour tests are usually not sufficiently realistic to evoke empathic-like behaviour; therefore we decided to ask owners about their experiences with their dogs in emotionally loaded situations. Owners from Hungary (N = 591) and from Germany (N = 2283) were asked to rate their level of agreement on a 1–5 Likert scale with statements about the reactivity of their dogs to their emotions and to other dogs’ behaviour. We created… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…However, the effect of the region of residence on some PCs suggests that cultural factors of the owner may also influence the perception of the pets’ personalities [ 13 ]. Some recent reports on the dog-human relationship seem to confirm the link between owner and perceived or actual animal personality [ 12 , 13 , 14 , 15 ]. Cimarelli et al [ 12 ] showed relationships between owner personality, interaction style, age, and dog behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the effect of the region of residence on some PCs suggests that cultural factors of the owner may also influence the perception of the pets’ personalities [ 13 ]. Some recent reports on the dog-human relationship seem to confirm the link between owner and perceived or actual animal personality [ 12 , 13 , 14 , 15 ]. Cimarelli et al [ 12 ] showed relationships between owner personality, interaction style, age, and dog behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Cimarelli et al [ 12 ] showed relationships between owner personality, interaction style, age, and dog behaviour. Sümegi et al [ 15 ] hypothesized the presence of emotional contagion, Szaánthó [ 14 ] of empathy, while other authors [ 13 , 55 ] reported similarity or complementarity between the personality profiles of dogs and owners. Assuming that owner personality is influential, the perceived differences between species remain challenging to explain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, on a multimodal level combining visual with acoustic stimuli, dogs can extract, integrate, and discriminate humans’ as well as conspecifics’ emotional expressions (Albuquerque et al 2016 ). Focussing particularly on empathy, a recent questionnaire study investigated dog owners’ evaluation of empathic-like responding in their dogs (Szánthó et al 2017 ). However, apart from this first survey-based approach of the topic, previous studies focussed on behavioural observations of dogs confronted with emotional situations in an intraspecies context and an interspecies context.…”
Section: Introductionmentioning
confidence: 99%